2021
DOI: 10.1042/bcj20210171
|View full text |Cite
|
Sign up to set email alerts
|

CLN5 and CLN3 function as a complex to regulate endolysosome function

Abstract: CLN5 is a soluble endolysosomal protein whose function is poorly understood. Mutations in this protein cause a rare neurodegenerative disease, Neuronal Ceroid Lipofuscinosis. We previously found that depletion of CLN5 leads to dysfunctional retromer, resulting in the degradation of the lysosomal sorting receptor, sortilin. However, how a soluble lysosomal protein can modulate the function of a cytosolic protein, retromer, is not known. In this work, we show that deletion of CLN5 not only results in retromer dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 48 publications
(89 reference statements)
3
30
0
Order By: Relevance
“…Although we did not measure lysosomal area in our iPSC-derived CLN5-deficient human neurons, we noticed an increased number of non-motile lysosomes (Figure 4B) and an increase in lysosomal intensity in the cell body (Figure 2A: second, third, and fourth panels) of CLN5-deficient neurons, with the overall lysosomal mass remaining the same (Figure 2E). The increased number of non-motile lysosomes and impaired anterograde lysosomal movement explain the accumulation of lysosomes in the cell bodies of the CLN5-deficient neurons (Figure 2A: second, third, and fourth panels, and Video S1B,C), as reported by Uusi-Rauva et al Yasa et al (2021) [14] suggested that CLN5 KO HeLa cells were not able to move lysosomes as efficiently as wild-type HeLa cells. In our study, the impaired anterograde movement in the CLN5-deficient human neurons could indicate that the neuronal projections are being exempt from having their waste cleared, which could cause neuronal toxicity at the synapses.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Although we did not measure lysosomal area in our iPSC-derived CLN5-deficient human neurons, we noticed an increased number of non-motile lysosomes (Figure 4B) and an increase in lysosomal intensity in the cell body (Figure 2A: second, third, and fourth panels) of CLN5-deficient neurons, with the overall lysosomal mass remaining the same (Figure 2E). The increased number of non-motile lysosomes and impaired anterograde lysosomal movement explain the accumulation of lysosomes in the cell bodies of the CLN5-deficient neurons (Figure 2A: second, third, and fourth panels, and Video S1B,C), as reported by Uusi-Rauva et al Yasa et al (2021) [14] suggested that CLN5 KO HeLa cells were not able to move lysosomes as efficiently as wild-type HeLa cells. In our study, the impaired anterograde movement in the CLN5-deficient human neurons could indicate that the neuronal projections are being exempt from having their waste cleared, which could cause neuronal toxicity at the synapses.…”
Section: Discussionsupporting
confidence: 74%
“…An effector of RAB7A, RILP, regulates the activity of V-ATPase, the key component for maintaining the acidity in the lysosomal lumen [32]. Interestingly, loss of CLN5 leads to reduced RAB7A/RILP interaction [14], which could lead to even further reduction in acidity in peripheral lysosomes, as seen in Figure 2A (second, third, and fourth panels).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Evidence in these models and in patient cells suggests the accumulation of autophagosomes/autolysosomes arises from reduced autophagic degradation ( Figure 3 ) ( Cao et al, 2006 ; Chang et al, 2011 ; Vidal-Donet et al, 2013 ; Lojewski et al, 2014 ; Chandrachud et al, 2015 ; Petcherski et al, 2019 ). The mechanisms causing reduced autophagic degradation upon CLN3 -deficiency are incompletely understood but may be linked to altered RAB7-mediated trafficking and/or altered Ca 2+ signalling ( Figure 3 ) ( Huber et al, 2014 ; Chandrachud et al, 2015 ; Petcherski et al, 2019 ; Yasa et al, 2020 ; Yasa et al, 2021 ). Thus, restoration of autophagic degradation in CLN3 -deficiency models has emerged as a promising therapeutic target ( Chang et al, 2011 ; Chandrachud et al, 2015 ; Hong et al, 2016 ; Palmieri et al, 2017 ; Petcherski et al, 2019 ; Kinarivala et al, 2020 ).…”
Section: The Roles Of Cln Genes and Proteins In Au...mentioning
confidence: 99%